Acute myocardial infarction-related mortality among older adults (≥65 years) with malignancy in the U.S. from 1999 to 2020 - Muhammad Abdullah Naveed; Sivaram Neppala; Himaja Dutt Chigurupati; Ahila Ali; Muhammad Omer Rehan; Ayman Fath; Bazil Azeem; Rabia Iqbal; Manahil Mubeen; Hamza Naveed; Muhammad Naveed Uz Zafar; Mushood Ahmed; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Acute Myocardial Infarction (AMI) in malignancy is a global threat, causing significant mortality and economic burden. They share common risk factors, highlighting the urgency of addressing this critical issue. Objective: This study analyzed demographic trends and disparities in mortality rates due to AMI in malignancy among adults aged 65 and older from 1999 to 2020. Methods: We used the CDC WONDER database to analyze Age-adjusted mortality rates (AAMRs) for AMI in malignancy patients (ICD-10 I21, C00-C97) from 1999 to 2020, stratifying by sex, race, geography, and metropolitan status. We calculated Average Annual Percentage Changes (AAPCs) and Annual Percentage Changes (APCs) per 100,000 with 95 % confidence intervals (CI) using Joinpoint regression. Results: Between 1999 and 2020, AMI in malignancy accounted for 172,691 deaths among adults aged ≥65 years, with the majority of deaths occurring in medical facilities (56.9 %). The overall AAMR for AMI in malignancy-related deaths decreased from 30.2 in 1999 to 14.2 in 2020, with an AAPC of −3.90 (p < 0.000001). Men showed higher AAMRs than women (28.6 vs. 12.3), with a more pronounced decrease in men (AAPC: 4.22, p < 0.000001) compared to women (AAPC: 3.78, p < 0.000001). Black individuals have the highest AAMR (22.7), followed by Whites (19.3). Arkansas had the highest AAMR (32.3), while Nevada had the lowest (8.1), with the Northeastern region having the highest regional AAMR (20.2), and nonmetropolitan areas had higher AAMRs. Conclusion: This study reveals significant demographic disparities in mortality rates related to AMI in malignant older adults. These findings emphasize the need for targeted interventions and improved access to care.